A weighty issue revisited: the dynamic effect of body weight on earnings and satisfaction in Germany - Frieder Kropfhäußer; Marco Sunder (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
We estimate the effect of changes in the body mass index on wages and satisfaction in a panel of German employees. Dynamic models indicate that satisfaction with life in general and with health are responsive to weight changes, but wages and satisfaction with work are not. These results mainly corroborate earlier findings from static panel or cross-sectional models.
Keywords: J24; J71; I31; 330